2020
DOI: 10.1016/j.seizure.2020.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ketogenic diet on platelet counts and global coagulation tests in childhood epilepsy

Abstract: Several antiseizure drugs (ASD), especially Valproic acid (VPA), influence platelet counts and coagulation parameters. The ketogenic diet (KD), established in drug-resistant epilepsy, is combined with ASDs. Bruising and prolonged bleeding times during KD have been described, but whether hemostatic changes result from the KD or from concomitant ASDs, remains unclear. Aim of the present study was to evaluate bleeding, platelet counts and global coagulation tests prior to and during KD in childhood epilepsy. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Further study of six patients revealed increased bleeding time and diminished platelet reactivity to aggregating factors, suggesting altered membrane dynamics secondary to lipid changes [ 66 ]. However, a more recent study of 162 children on a KD for epilepsy found no differences in platelet counts or function after one year on the KD [ 68 ]. In this study, it was also shown that desmopressin was able to stimulate clotting in vitro, suggesting a possible treatment for patients with concerning bruising [ 66 ].…”
Section: Complications Of a Ketogenic Diet By Systemmentioning
confidence: 99%
“…Further study of six patients revealed increased bleeding time and diminished platelet reactivity to aggregating factors, suggesting altered membrane dynamics secondary to lipid changes [ 66 ]. However, a more recent study of 162 children on a KD for epilepsy found no differences in platelet counts or function after one year on the KD [ 68 ]. In this study, it was also shown that desmopressin was able to stimulate clotting in vitro, suggesting a possible treatment for patients with concerning bruising [ 66 ].…”
Section: Complications Of a Ketogenic Diet By Systemmentioning
confidence: 99%
“…However, Dressler et al noted no coagulation abnormalities in a consecutive series of 162 children receiving the KD. 18 Serial measurements of platelet counts and global coagulation tests (aPTT, PT, and fibrinogen) were obtained at baseline and during KD therapy (at 1, 3, 6 and 12 months). The authors noted no clinical bleeding either during routine activities of daily life or during surgery and no clinically significant abnormalities in coagulation function; however, platelet function was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Al revealed mild thrombocytosis in epileptic pediatric patients at baseline which subsequently normalized while on a ketogenic diet in all patient groups within 6 months. The baseline elevation in platelet count in the epileptic population is thought to be due to underlying inflammation [32]. The ketogenic diet has been shown to have anti-inflammatory properties by reducing IL-8 Beta levels in the brain and plasma [33].…”
Section: Factors Decreasing Platelet Countmentioning
confidence: 99%